Study on particle cluster dynamics behavior in settling and the influence by fiber barrier - Bai, Zhifeng; Li, Mingzhong; Li, Feng; Du, Qiuying (Frontiers in Materials, 2022)
The dispersion of particle clusters is relevant to a high concentration carrying fluid such as fracturing and drilling fluid, and the fiber-containing fluid could improve the carrying performance of particles. In the present study, the settling dynamics behavior of clusters is investigated using the CFD-DEM method. The numerical simulation method employed was able to accurately predict the deformation and velocity change rules, which express the cluster settling dynamics behavior. The velocity variation of particles is affected by hindered and contact inside the cluster, and the velocity contrast leads to particle leakage and cluster deformation. The cluster will have regular shape changes and break up in the settlement process under gravity and fluid drag force. According to the sensitivity parameter analysis, the deformation of clusters is mainly affected by the fluid rheological properties. Different from glycerol, the settling cluster in viscoelastic HPG has a more complex dynamic behavior and a better fiber barrier effect. The fiber barrier between particles in the cluster can be regarded as a weakly constrained fiber grid structure. Due to the contact force, fiber grid structure formed in the cluster could effectively restrain the shape change and break up trend in the settlement process. The design also consider about the influence of fiber and HPG concentration, we analyze the settling velocity of the mixed fiber cluster. Overall, the research on the cluster settling dynamics behavior is helpful to analyze the effect of fiber-containing fluid in carrying.